Pengaruh Lingkungan Kerja Fisik Terhadap Kinerja Karyawan PT. XYZ - Amelia Syahada (Universitas Pahlawan Tuanku Tambusai, 2024)
The work environment is one of the external factors that affect maximum work results in each job. The work environment has a direct influence on employees who carry out work within the company. Based on the measurement results at PT. XYZ found that the light in the office is less evenly distributed, ranging from 50 lux to 85 lux where the standard is not in accordance with Permenaker No. 5 of 2018. The lack of supporting facilities such as air conditioners in each field, it is not in accordance with SNI 03-6572-2001. Based on the results of processing questionnaire data from 2 variables of the work environment (X1 = lighting and X2 = air circulation) there is no influential variable where (X1) with the Asymp value. Sig 0.147 and (X2) with Asymp values. Sig 1 where both variables are equally more than 0.05, meaning Ho is accepted and H1 is rejected. The results of the research will be given to PT. XYZ in the form of recommendations. It is hoped that with these results known, the company can consider changes in the physical work environment in the workspace of PT. XYZ to be better and conducive.